The Effect of Green Innovation on Company Sustainability Performance With CEO Tenure As a Moderating Variable - Andi Harmoko Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Abstract This research aims to determine green innovation on company sustainability and whether there is a tenured CEO who plays a moderating role. This research uses a sampling method in the form of non-probability sampling. The sampling technique used in this research used purposive sampling. The analytical method used in this research is a quantitative analysis method. The results of this research show that green innovation has a significant effect on company sustainability. And the CEO is able to moderate green innovation towards company sustainability .